Xylaria sridharii sp. nov.—a new species of Xylariaceae from India - Sharathchandra, Kodandoor; Mahadevakumar, Shivannegowda; Nuthan, Bettadapura R.; Satish, Shreedharamurthy (Phytotaxa, 2023)
A new species of Xylaria associated with leaflets of coconut (Cocos nucifera) in Konaje, Mangalore, Karnataka is collected and examined. The species was characterized by having long stromata terminated with a globose head-like swollen fertile part, which showed a further extended thread-like appendage at its tip. Micro-morphological examination, cultural characterization and molecular sequence analysis of ITS-rDNA, LSU and TUB were carried out. The phylogenetic analysis based on combined ITS-rDNA and tub2 gene sequences showed that Xylaria sridharii is phylogenetically related to X. oxyacanthae, X. reevesiae and X. palmicola. However, X. sridharii is distinguished by the presence of the hirsute stromata, which shows multiple branching (2–4, but rarely recorded up to 6) at the apex, and each branch produces a fertile part, which in turn ends with a thin filiform appendage.